Digestible lysine supplementation influences weight gain in 21-day-old broiler chickens - Quadros, T. O. [UNESP]; Duarte, K. F.; Sgavioli, S.; Alva, J. C.R.; Domingues, C. H.; Santos, E. T. [UNESP]; Castiblanco, D. M.C. [UNESP]; Marques, R. H.; Amoroso, L. [UNESP]; Junqueira, O. M. [UNESP] (Cordoba University Press (UCOPress), 2019)
This study analysed the effects of digestible lysine on the performance parameters, morphometry and quality of the breast muscle (Pectoralis major) of Cobb 500 broiler chickens aged 21 and 42 days. Two completely randomized experiments were performed, with five treatments and eight replications of 30 birds per treatment. The diets were adjusted according to the nutritional requirements for each phase of poultry development, with digestible lysine levels during the initial phase (birds aged 1 to 21 days) at 1.12, 1.19, 1.25, 1.31, and 1.37% and during the final phase (22 to 42 days) at 0.97, 1.02, 1.08, 1.13, and 1.19%. During the initial phase, lysine supplementation had a significant effect (P<0.05) on weight gain and red content in breast meat, with 1.24% and 1.29% digestible lysine resulting in maximum weight gain and red content, respectively. No significant difference (P>0.05) was observed in breast muscle morphometry, carcass yield, performance, or meat quality in birds aged 22-42 days for the different levels of lysine, suggesting that the lowest level of lysine tested did not have a negative impact on production characteristics even though it was below the recommended levels for this species. In conclusion, 1.24% digestible lysine is recommended for maximum weight gain at the initial phase of broiler chicken development (1-21 days) and 0.97% is sufficient to meet the nutritional requirements of birds at the final phase (22-42 days) without compromising production performance.
Suplementação de lisina digestível influencia o ganho de peso de frangos de corte aos 21 dias de idade
Keywords: Digestible amino acids; Ideal protein; Performance; Regression analysis